Efficient hydrogen production on MoNi 4 electrocatalysts with fast water dissociation kinetics - Zhang, Jian; Wang, Tao; Liu, Pan; Liao, Zhongquan; Liu, Shaohua; Zhuang, Xiaodong; Chen, Mingwei; Zschech, Ehrenfried; Feng, Xinliang (Nature Communications, 2017)
Various platinum-free electrocatalysts have been explored for hydrogen evolution reaction in acidic solutions. However, in economical water-alkali electrolysers, sluggish water dissociation kinetics (Volmer step) on platinum-free electrocatalysts results in poor hydrogen-production activities. Here we report a MoNi4 electrocatalyst supported by MoO2 cuboids on nickel foam (MoNi4/MoO2@Ni), which is constructed by controlling the outward diffusion of nickel atoms on annealing precursor NiMoO4 cuboids on nickel foam. Experimental and theoretical results confirm that a rapid Tafel-step-decided hydrogen evolution proceeds on MoNi4 electrocatalyst. As a result, the MoNi4 electrocatalyst exhibits zero onset overpotential, an overpotential of 15 mV at 10 mA cm-2 and a low Tafel slope of 30 mV per decade in 1 M potassium hydroxide electrolyte, which are comparable to the results for platinum and superior to those for state-of-the-art platinum-free electrocatalysts. Benefiting from its scalable preparation and stability, the MoNi4 electrocatalyst is promising for practical water-alkali electrolysers.
CRIS-Team Scopus Importer:2023-03-20